2020
DOI: 10.4236/gep.2020.82008
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Hexavalent Chromium from Aqueous Solution by Adsorption on Palm Oil Fuel Ash (POFA)

Abstract: This study investigated the removal of hexavalent chromium, Cr(VI) from aqueous solution by adsorption using palm oil fuel ash (POFA), an agricultural waste from the palm oil industry. POFA adsorbent was characterized by X-ray diffraction (XRD) analysis. Batch adsorption study revealed that the optimum conditions for the removal were as follows: pH 2, adsorbent dosage 80 g/L and contact time of 6 min, which resulted in 92% removal and 0.464 mg/g maximum adsorption capacity. Adsorption isotherm and kinetic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
(26 reference statements)
0
12
0
1
Order By: Relevance
“…Oil palm fuel ash pH = 2, 200 rpm, 80 g/L of adsorbent 0.462 [5] Banana peel dust pH = 1, 0.4 g of adsorbent dose, 300 rpm, 50 • C 26.46 [12] Modified lychee peel 50 • C, pH = 2, 130 rpm, 0.08 g of adsorbent and 20 mL of solution 9.76 [17] Foxtail millet shell 4 g/L of adsorbent dose, 0.25-0.35 mm of particle size, 30 mL of solution, 120 min, 350 rpm, and 25…”
Section: Adsorbentmentioning
confidence: 99%
See 2 more Smart Citations
“…Oil palm fuel ash pH = 2, 200 rpm, 80 g/L of adsorbent 0.462 [5] Banana peel dust pH = 1, 0.4 g of adsorbent dose, 300 rpm, 50 • C 26.46 [12] Modified lychee peel 50 • C, pH = 2, 130 rpm, 0.08 g of adsorbent and 20 mL of solution 9.76 [17] Foxtail millet shell 4 g/L of adsorbent dose, 0.25-0.35 mm of particle size, 30 mL of solution, 120 min, 350 rpm, and 25…”
Section: Adsorbentmentioning
confidence: 99%
“…Several removal methods have been used in the capture of hexavalent chromium due to its toxic health effects [5]. These technologies include filtration, chemical precipitation, Water 2022, 14, 844 2 of 15 adsorption, electrodeposition and membrane systems or even ion exchange processes [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…He also considers Langmuir's adsorption-desorption kinetics and considers that the driving force is governed by reversible second-order kinetics; however, q0 and kT are treated as empirical parameters that are estimated by fitting the model to experimental data [46]. On the other hand, the Yon-Nelson model assumes that the rate of decrease in the probability of adsorption of each adsorbate molecule is proportional to the probability of adsorbate advancement in the adsorbent [47]. According to the correlation coefficient (R 2 ) it was established was found that Thomas and Yoon-Nelson's model moderately describe the experimental data by a similar fit of 0.599 and 0.612 respectively, while the other 2 models were further away, so it is suggested that for the scaling up of this type of processes work should be done on the development of an own model [48].…”
Section: Breakage Curvementioning
confidence: 99%
“…Various adsorbents have been tested for the removal of heavy metals from aqueous solutions with promising results based on living biomass (fungi, algae, and bacteria) and agricultural biomass (husks, sawdust, agricultural and agroindustrial wastes) [13][14][15][16][17]. Different lignocellulosic biomasses have been used in heavy metal remotion, such as millet [18], lime [19,20], rice husks [18,21], black walnut bark [22], eucalyptus [23], palm residues [24], plantain [25], and kenaf [26], among others [27][28][29][30][31], presenting high removal yields. The use of bio adsorbents of residual lignocellulosic origin has advantages, such as low cost, high availability, and excellent performance at high and low concentrations [32].…”
Section: Introductionmentioning
confidence: 99%